2021
DOI: 10.20944/preprints202106.0726.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Utero Exposure to 9-Tetrahydrocannabinol Leads to Postnatal Catch-up Growth and Dysmetabolism in the Adult Rat Liver

Abstract: Rates of gestational cannabis use have increased despite limited evidence for its safety in fetal life. Recent animal studies demonstrate that prenatal exposure to 9-tetrahydrocannabinol (9-THC, the psychoactive component of cannabis) promotes intrauterine growth restriction (IUGR), culminating in postnatal metabolic deficits. Given IUGR is associated with impaired hepatic function, we hypothesized that 9-THC offspring would exhibit hepatic dyslipidemia. Pregnant Wistar rat dams received daily injections of ve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…This is consistent with the previous study in which obesity was observed in adult offspring following postnatal catch-up growth. 41 In this study, we found that maternal administration of SP has beneficial effects, such as lowering the liver to body weight ratio, diminishing adipocyte size, and decreasing serum and hepatic lipid levels, indicating a hypolipidemic effect of SP. Moreover, the increased RER implies the increased availability of fat as an energy source under SP administration and also suggests a possibility that the hypolipidemic effect of SP may be partially attributed to increased energy expenditure.…”
Section: Discussionmentioning
confidence: 56%
“…This is consistent with the previous study in which obesity was observed in adult offspring following postnatal catch-up growth. 41 In this study, we found that maternal administration of SP has beneficial effects, such as lowering the liver to body weight ratio, diminishing adipocyte size, and decreasing serum and hepatic lipid levels, indicating a hypolipidemic effect of SP. Moreover, the increased RER implies the increased availability of fat as an energy source under SP administration and also suggests a possibility that the hypolipidemic effect of SP may be partially attributed to increased energy expenditure.…”
Section: Discussionmentioning
confidence: 56%
“…In Long Evans, Wistar, and Sprague Dawley rats, lower birth weight was associated with daily in utero exposure to 15, 30, or 150 mg/kg (oral) cannabis extracts (130,131), 50 mg/kg (s.c.) THC (132), 3 mg/kg (i.p.) THC (133)(134)(135), or smoke from cannabis extracts (400 mg/mL) (130,(136)(137)(138)(139)(140). In contrast, no effect of PCE on birth weight was observed following daily in utero exposure to 0.5-10 mg/kg (oral) THC or CE (130,139,140), 2 mg/kg (s.c.) THC (141), or smoke from CEs (100 mg/mL) (142, 143).…”
Section: Birth Outcomes Associated With Pce In Rodentsmentioning
confidence: 99%